2016
DOI: 10.1128/cvi.00590-15
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal IgG Levels Correlate Better with Respiratory Syncytial Virus Load and Inflammation than Plasma IgG Levels

Abstract: Maternal vaccination is currently considered a strategy against respiratory syncytial virus (RSV) infections. In RSV-infected infants, high mucosal IgG levels correlated better with reduced RSV load and lower mucosal CXCL10 levels than plasma IgG levels. For future vaccination strategies against RSV, more focus should be on the mucosal humoral immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
4
26
0
1
Order By: Relevance
“…[43][44][45] Indeed, high titers of pre-existent mucosal IgG are correlated with reduced viral loads in hRSV-infected infants. 46 Similar correlation have been obtained for nasal IgA levels in naturally infection and in experimental challenges in healthy adults. 47,48 On the other hand, it has been described in mice that antibodies play a major role during reinfection, even more than in the first infection, giving a principal role to T cells in the clearance of the virus during the first hRSV challenge.…”
Section: The Humoral Response Against Hrsv Infectionsupporting
confidence: 65%
“…[43][44][45] Indeed, high titers of pre-existent mucosal IgG are correlated with reduced viral loads in hRSV-infected infants. 46 Similar correlation have been obtained for nasal IgA levels in naturally infection and in experimental challenges in healthy adults. 47,48 On the other hand, it has been described in mice that antibodies play a major role during reinfection, even more than in the first infection, giving a principal role to T cells in the clearance of the virus during the first hRSV challenge.…”
Section: The Humoral Response Against Hrsv Infectionsupporting
confidence: 65%
“…Vissers et al studied a cohort of infants hospitalized with RSV infection in the Netherlands to determine the importance of serum versus mucosal antibody, presumed to be maternally derived given the young age of the infants (mean, 53 days). The authors found that RSV-specific mucosal IgG concentrations, but not plasma IgG concentrations, inversely correlated with viral load (4). While the results are provocative, the study was limited by its small sample size and cross-sectional design.…”
mentioning
confidence: 78%
“…In this issue of Clinical and Vaccine Immunology, two articles address important obstacles in the path to a successful RSV vaccine (3,4). Acosta and colleagues provide a history and perspective on the vaccine-enhanced RSV illness that occurred in the 1960s.…”
mentioning
confidence: 99%
“…This is unlike other respiratory infections, such as with influenza virus, in which antibodies persist and confer lifelong protection against the original infecting strain. However, nasal anti-RSV IgA levels correlate with protection from experimental infection in adults 89 , while levels of nasal (maternally derived) anti-RSV IgG correlate with lower viral load in infants 90 . Furthermore, anti-RSV antibodies have been found in amniotic fluid 91 and could potentially be protective to the lungs of newborns.…”
Section: Adaptive Immune Responses To Rsvmentioning
confidence: 98%